The Influence of Parents' Religious Behavior On Motivation to Learn PAI (Islamic Religious Education) and Obedience to Worship - Ulfah Sari Rezeki; Tina Sheba Cornelia; Jainal B Togatorop (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Students consider Islamic religious lessons unimportant and difficult, so their learning motivation is low. This type of research is quantitative research. The population in this study was class VII SMPN 38 Medan Marelan which amounted to 147 students. The sampling technique in this study used the Slovin formula. The sampling technique used was random sampling. The sample in this study amounted to 99 people. Data analysis technique using r product moment. The results showed that in the calculation of the r product moment, the value of the r count is 0.353. This means if the value of rxy 0.353 > r table 0.1646 then the first hypothesis is accepted. That is, there is an influence between the religious behaviors of parents on the motivation to learn PAI in seventh-grade students of SMPN 38 Medan Marelan. There is a positive and significant influence on parents’ religious behavior on students' obedience to worship. This can be seen from the results of the correlation calculation using r product moment, the value of r count is 0.400. Based on the r-value obtained, it is necessary to consult the product-moment correlation coefficient in the table with N = 99 both at a significant level of 5%, a value of 0.1646 is obtained, and at a significant level of 1%, a value of 0.2312 is obtained. This means if the value of rxy 0.400 > r table 0.1646 then the second hypothesis is accepted.